2016
DOI: 10.1038/ncomms12741
|View full text |Cite
|
Sign up to set email alerts
|

Transport of a kinesin-cargo pair along microtubules into dendritic spines undergoing synaptic plasticity

Abstract: Synaptic plasticity often involves changes in the structure and composition of dendritic spines. Vesicular cargos and organelles enter spines either by exocytosing in the dendrite shaft and diffusing into spines or through a kinesin to myosin hand-off at the base of spines. Here we present evidence for microtubule (MT)-based targeting of a specific motor/cargo pair directly into hippocampal dendritic spines. During transient MT polymerization into spines, the kinesin KIF1A and an associated cargo, synaptotagmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 41 publications
6
69
0
Order By: Relevance
“…The increased exocytosis that occurs throughout the dendritic arbor is followed by movement of exocytosed syt4 within the plane of the membrane. Together these results indicate that MTs are indeed capable of transporting specific cargo into targeted dendritic spines, and, of importance, this directed targeting of cargo is highly disrupted in the absence of a particular motor protein, KIF1A (McVicker et al , 2016). Thus not only are MTs important for transporting material throughout the dendritic arbor, but they are also instrumental in sequestering vesicles and cargo away from the plasma membrane while it is en route to its destination.…”
Section: What Cargoes Are Microtubules Transporting Into or Out Of Spmentioning
confidence: 82%
See 3 more Smart Citations
“…The increased exocytosis that occurs throughout the dendritic arbor is followed by movement of exocytosed syt4 within the plane of the membrane. Together these results indicate that MTs are indeed capable of transporting specific cargo into targeted dendritic spines, and, of importance, this directed targeting of cargo is highly disrupted in the absence of a particular motor protein, KIF1A (McVicker et al , 2016). Thus not only are MTs important for transporting material throughout the dendritic arbor, but they are also instrumental in sequestering vesicles and cargo away from the plasma membrane while it is en route to its destination.…”
Section: What Cargoes Are Microtubules Transporting Into or Out Of Spmentioning
confidence: 82%
“…Four independent studies published within a year of one another demonstrated that MTs indeed enter spines in a synaptic activity–dependent manner (Gu et al , 2008; Hu et al , 2008; Mitsuyama et al , 2008; Jaworski et al , 2009). It is also clear, as demonstrated by live-cell microscopy, that all of the MT polymerization events into spines are transitory, averaging only a few minutes at a time (Hu et al , 2008, 2011; Jaworski et al , 2009; Kapitein et al , 2011; Merriam et al , 2011, 2013; Wagner et al , 2011; McVicker et al , 2016). Moreover, the presence of MTs in spines in fixed neurons required rapid fixation and the use of MT-stabilizing buffer (Gu et al , 2008; Hu et al , 2008; Mitsuyama et al , 2008).…”
Section: Microubule Dynamics and Dendritic Spinesmentioning
confidence: 96%
See 2 more Smart Citations
“…The receptor transport to the spines becomes dependent on the other transport mechanisms (e.g. exocytosis of vesicles in the dendritic shafts or a myosin-based transport (40). As a result, reduced receptor signalling (e.g.…”
Section: Model Of the Role Of Bbs Proteins In Synapsesmentioning
confidence: 99%